The dynamic genomes of Hydra and the anciently active repeat complement of animal chromosomes - Kon-Nanjo, Koto; Kon, Tetsuo; Koubková Yu, Tracy Chih-Ting; Rodriguez-Terrones, Diego; Falcon, Francisco; Martínez, Daniel E.; Steele, Robert E.; Tanaka, Elly Margaret; Holstein, Thomas W.; Simakov, Oleg (Genome biology, 2025)
Background: Many metazoan genomes are characterized by highly conserved chromosomal homologies that predate the ancient origin of this clade. This conservation has been tested by expansions of selfish DNA elements, in particular transposable elements (TEs). While comparative genomics studies have highlighted their diversity across animal genomes, common principles underlying their evolution along deeply conserved chromosomes have been elusive. A detailed mechanistic understanding from phylogenetically key and early branching animal species has been lacking. Results: We present a comprehensive stem-cell resolved genomic and transcriptomic study of the freshwater cnidarian Hydra, an animal characterized by its high regenerative capacity, the ability to propagate clonally, and an apparent lack of aging. Using single-haplotype telomere-to-telomere genome assemblies of two recently diverged strains and utilizing unique features of hydra biology allowed us to sequence and compare the individual genomes of hydra’s three stem cell lineages. We show that distinct TE families are active at both transcriptional and genomic levels via non-random insertions in each of these lineages. We show that the core set of these active TE families, primarily composed of DNA elements, is evolutionarily deeply conserved and contributes to consistent genomic expansions in metazoan lineages. These anciently active TEs differentially contribute to structural variants around loci associated with cell proliferation and long-range topological contacts. This is in strong contrast to the frequently observed and highly varied substantial genome expansions that often happen via retroelements.Conclusions: Our study suggests an ancient and conserved role for these core TEs as self-renewing components of animal chromosomes.